Cytomegalovirus infection in pediatric rheumatic diseases: a review - Wolf Dana G; Eisenstein Eli M (BMC, 2010)
Abstract Human cytomegalovirus (HCMV) is familiar to pediatric rheumatologists mainly as a cause of opportunistic disease in pharmacologically immune suppressed patients. However, HCMV also has a variety of immuno-modulatory effects, through which it may influence the course of rheumatic conditions. In this article we discuss the interplay between HCMV and the immune system, and review the clinical manifestations, diagnosis, and treatment of HCMV infection in children with rheumatic disease.